2001
DOI: 10.1161/hs1101.098356
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Near-Infrared Spectrometer (NIRO 300) for the Detection of Intracranial Oxygenation Changes in the Adult Head

Abstract: Background and Purpose-The clinical application of intracranial near-infrared spectroscopy in adults has been hampered by concerns over contamination from extracranial tissues. The NIRO 300 (Hamamatsu Photonics) provides continuous online measurements of hemoglobin and cytochrome oxidase concentrations and a calculated tissue oxygen index (TOI). The present study seeks confirmation of the anatomic source of TOI in the adult cranium. Methods-Sixty patients undergoing carotid endarterectomy were studied. The NIR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
159
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(168 citation statements)
references
References 44 publications
7
159
1
1
Order By: Relevance
“…It (Al-Rawi et al, 2001), and the MD fNIRI methodology is superior to the traditional MBLL approach in excluding extracranial hemodynamic changes (Canova et al, 2011); but MD fNIRI does not completely remove changes in the extracerebral compartment (Davie and Grocott, 2012). The original MD NIRI approach was extended to two-layer models (Choi et al, 2004;Fabbri et al, 2004) and ultimately to five-layer models (Yamada et al, 2009(Yamada et al, , 2010, the last one including also μ s ′ changes in the modeling.…”
Section: Multivariate Methods Of Typementioning
confidence: 99%
See 1 more Smart Citation
“…It (Al-Rawi et al, 2001), and the MD fNIRI methodology is superior to the traditional MBLL approach in excluding extracranial hemodynamic changes (Canova et al, 2011); but MD fNIRI does not completely remove changes in the extracerebral compartment (Davie and Grocott, 2012). The original MD NIRI approach was extended to two-layer models (Choi et al, 2004;Fabbri et al, 2004) and ultimately to five-layer models (Yamada et al, 2009(Yamada et al, , 2010, the last one including also μ s ′ changes in the modeling.…”
Section: Multivariate Methods Of Typementioning
confidence: 99%
“…scalp skin, subcutaneous tissue, aponeurosis, connective tissue, periosteum, cranium, meninges (dura mater, arachnoid mater, pia mater), cerebrospinal fluid (CSF) (Ellis, 2012)) since the light is both introduced and collected at the surface of the scalp. For a single source-detector arrangement, it was shown the light intensity is~10-20 times (depending on the model for estimating the hemodynamic signals and the SDS) more sensitive to the extracerebral compartment compared to the cerebral compartment (Al-Rawi et al, 2001;Liebert et al, 2004). The tissue-specific energy of light absorbed in the head by using a 3 cm SDS was investigated by Haeussinger et al (2011) by a Monte Carlo simulation based on three-dimensional segmented structural MRI data.…”
Section: Classification Of Signal Componentsmentioning
confidence: 99%
“…Although it does not specifically attempt to exclude any contribution from extracranial blood, a degree of compensation does occur which is intrinsic to the algebraic differentiation of the attenuation gradient measured by the multichannel detector. Recently, using the NIRO 300 to investigate cerebral oxygenation changes during carotid surgery, the sensitivity of TOI to intracranial changes was 87.5% with a specificity of 100% [21]. In contrast, the sensitivity and specificity to extracranial changes were 0%, suggesting that TOI, as measured by the NIRO 300, reflects changes in cerebral tissue oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…The NIRO 300 has also recently ................................................................................................................................................................................................................... Ó 2002 Blackwell Publishing Ltd been released but its predecessor, the NIRO 500, has similarly been compared with jugular venous oximetry and measurements of brain tissue pO 2 [28] and also with the INVOS 3100 [3,27]. There are few published studies to validate TOI as an independent monitor of cerebral oxygenation [29] but the recent report demonstrating high sensitivity and specificity for intracranial changes is likely to stimulate interest in its use in the clinical setting [21]. However, validation of new devices is complicated by the absence of a Ôgold standardÕ against which monitors of cerebral oxygenation can be tested at the bedside.…”
Section: Discussionmentioning
confidence: 99%
“…However, the scattering factor included in the TIO calculation make spatially resolved spectroscopy less reliable for multilayered structure like in cerebral oxygenation measurements. However, Al-Rawi et al (2001) showed that the NIRO 300, a spatially resolved spectrometer, has a high degree of sensitivity and specificity to intracranial and extracranial changes. SRS is technically simpler than TRS and provides measurements with a good signal-to-noise ratio and a high time resolution (Perrey, 2008).…”
Section: Spatially Resolved Spectroscopymentioning
confidence: 99%